2009
DOI: 10.1021/tx800355k
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein-Derived DNA Adduct Formation in Human Colon Cancer Cells: Its Role in Apoptosis Induction by Docosahexaenoic Acid

Abstract: The apoptotic effects of docosahexaenoic acid (DHA) and other ω-3 polyunsaturated fatty acids (PUFAs) have been documented in cell and animal studies. The molecular mechanism by which DHA induces apoptosis is unclear. Although there is no direct evidence, some studies have suggested that DNA damage generated through lipid peroxidation may be involved. Our previous studies showed that DHA, because it is high degree of unsaturation, can give rise to the acrolein-derived 1,N2-propanodeoxyguanosine (Acr-dG) as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…It was reported that acrolein caused apoptosis in the colon cancer cells by production of a cellular stress response [23,24]. In this study, we demonstrated that acrolein can cause cardiac myocytes injury and cell death in concentrationdependent manner.…”
Section: Acrolein-induced Cardiomyocytes Apoptosissupporting
confidence: 51%
“…It was reported that acrolein caused apoptosis in the colon cancer cells by production of a cellular stress response [23,24]. In this study, we demonstrated that acrolein can cause cardiac myocytes injury and cell death in concentrationdependent manner.…”
Section: Acrolein-induced Cardiomyocytes Apoptosissupporting
confidence: 51%
“…Acrolein-induced necrosis was described in few studies (Luo et al, 2005), but mitochondrial-driven cell death seems to be the canonical road and was widely studied. Acrolein-induced apoptosis was indeed confirmed in several cell types through DNA fragmentation, phosphatidylserine externalization, poly(ADP-ribose) polymerase cleavage and activation of caspases (Pan et al, 2009;Roy et al, 2010). Last but not least, hydroxyalkenals are potent activators of apoptosis.…”
Section: Lc50 µM Referencesmentioning
confidence: 97%
“…In a recent study, correlations were established between AdG formation and DHA-induced apoptotic response, by measuring caspase-3 activity and poly(ADP-ribose) polymerase cleavage, as well as cell cycle arrest in human colon cancer cells. These results suggest an association between AdG adduct formation and the protective effect of DHA against colon tumorigenesis [65]. The potential role of AdG as the ''good'' adduct is intriguing.…”
Section: Dietary Factorsmentioning
confidence: 88%